Factors Affecting Entrepreneurial Intention Among University Students in Himachal Pradesh, India (Journal of Development and Social Engineering, 2023)
Entrepreneurship has emerged as a driving force for economic growth, innovation, and job creation This study aims find out the factors affecting entrepreneurial intention of university students in Himachal Pradesh, India. For this purpose, a sample of 200 students, who were pursuing postgraduation and under graduation in different universities across diverse academic disciplines were taken purposively. Both descriptive as well as inferential statistics were used for the analysis. The researcher used partial least square structural equation modelling (PLS-SEM) to see the relationship between different independent factors and entrepreneurial intention. The results revealed that prior entrepreneurship exposure and self-efficacy have statistically significant and positive impact on entrepreneurial intentions. However, the study found that entrepreneurial attitude, entrepreneurship education and risk- taking behaviour have no significant impact on entrepreneurial intention. This highlights the importance of real world experience and self-belief in fostering the desire to engage in entrepreneurship. This research serves as a foundation for future studies and policy initiatives aimed at fostering an entrepreneurial development in Himachal Pradesh.